Minimal mortality and rapid recovery of the dominant shrub Larrea tridentata following an extreme cold event in the northern Chihuahuan Desert. (25th July 2019) - Ladwig, Laura M.; Collins, Scott L.; Krofcheck, Dan J.; Pockman, William T.
Abstract: Questions: Woody encroachment into grasslands is a worldwide phenomenon partially influenced by climate change, including extreme weather events. Larrea tridentata is a common shrub throughout the warm deserts of North America that has encroached into grasslands over the past 150 years. Physiological measurements suggest that the northern distribution of L. tridentata is limited by cold temperatures; thus extreme winter events may slow or reverse shrub expansion. We tested this limitation by measuring the response of individual L. tridentata shrubs to an extreme winter cold (−31°C) event to assess shrub mortality and rate of recovery of surviving shrubs. Location: Sevilleta National Wildlife Refuge, Socorro County, New Mexico, USA. Methods: Canopy dieback and recovery following an extreme cold event were measured for 869 permanently marked individual L. tridentata shrubs in grass–shrub ecotone and shrubland sites. Individual shrubs were monitored for amount of canopy dieback, rate of recovery, and seed set for three growing seasons after the freeze event. Results: Shrubs rapidly suffered a nearly complete loss of canopy leaf area across all sites. Although canopy loss was high, mortality was low and 99% of shrubs resprouted during the first growing season after the freeze event. Regrowth rates were similar within ecotone and shrubland sites, even when damage by frost was larger in the latter. After three years of recovery, L. tridentata canopies had regrown on average 23–83% of the original pre‐freeze canopy sizes across the sites. Conclusions: We conclude that isolated extreme cold events may temporarily decrease shrubland biomass but they do not slow or reverse shrub expansion. These events are less likely to occur in the future as regional temperatures increase under climate change. Abstract : A single extreme cold event did not slow or reverse shrub encroachment of a cold‐intolerant desert shrub ( Larrea tridentata ). Although extreme cold temperatures caused extensive canopy mortality across Chihuahuan Desert shrublands, damage was less for individuals in the shrubland–grassland ecotone and nearly all (99%) shrubs regrew.